The Determinants of Publication Rates of Faculty Members at a Canadian University - Dickson, Vaughan A (Canadian Journal of Higher Education, 1983)
This paper examines the determinants of inter-individual differences in publica- tion rates for a sample of faculty members in a Canadian university. A simple model of publication output is presented and tested with an ordinary least squares regression. Among the conclusions are that academic rank, degree qualifications, academic discipline and the number of years since receipt of first degree significantly influence publication rates.